Comprehensive 7 T CEST: A clinical MRI protocol covering multiple exchange rate regimes - Fabian, Moritz; Rajput, Junaid Rasool; Schüre, Jan-Rüdiger; Weinmüller, Simon; Mennecke, Angelika; Möhle, Tim Alexius; Rampp, Stefan; Schmidt, Manuel; Dörfler, Arnd; Zaiß, Moritz (NMR in Biomedicine, 2024)
SECTIONSPDFPDFTOOLS SHARE Abstract Chemical exchange saturation transfer (CEST) is a magnetic resonance (MR) imaging method providing molecular image contrasts based on indirect detection of low concentrated solutes. Previous CEST studies focused predominantly on the imaging of single CEST exchange regimes (e.g., slow, intermediate or fast exchanging groups). In this work, we aim to establish a so-called comprehensive CEST protocol for 7 T, covering the different exchange regimes by three saturation B1 amplitude regimes: low, intermediate and high. We used the results of previous publications and our own simulations in pulseq-CEST to produce a 7 T CEST protocol that has sensitivity to these three B1 regimes. With postprocessing optimization (simultaneous mapping of water shift and B1, B0-fitting, multiple interleaved mode saturation B1 correction, neural network employment (deepCEST) and analytical input feature reduction), we are able to shorten our initially 40 min protocol to 15 min and generate six CEST contrast maps simultaneously. With this protocol, we measured four healthy subjects and one patient with a brain tumor. We established a comprehensive CEST protocol for clinical 7 T MRI, covering three different B1 amplitude regimes. We were able to reduce the acquisition time significantly by more than 50%, while still maintaining decent image quality and contrast in healthy subjects and one patient with a tumor. Our protocol paves the way to perform comprehensive CEST studies in clinical scan times for hypothesis generation regarding molecular properties of certain pathologies, for example, ischemic stroke or high-grade brain tumour

Controlling sharpness, SNR, and specific absorption rate for 3D fast-spin echo at 7T by end-to-end learning - Dawood, Peter; Blaimer, Martin; Herrler, Jürgen; Liebig, Patrick; Weinmüller, Simon; Malik, Shaihan; Jakob, Peter M.; Zaiß, Moritz (Magnetic Resonance in Medicine, 2025)
Purpose: To non-heuristically identify dedicated variable flip angle (VFA) schemes optimized for the point-spread function (PSF) and SNR of multiple tissues in 3D FSE sequences with very long echo trains at 7T. Methods: The proposed optimization considers predefined specific absorption rate (SAR) constraints and target contrast using an end-to-end learning framework. The cost function integrates components for contrast fidelity (SNR) and a penalty term to minimize image blurring (PSF) for multiple tissues. By adjusting the weights of PSF/SNR cost-function components, PSF- and SNR-optimized VFAs were derived and tested in vivo using both the open-source Pulseq standard on two volunteers as well as vendor protocols on a 7T MRI system with parallel transmit extension on three volunteers. Results: PSF-optimized VFAs resulted in significantly reduced image blurring compared to standard VFAs for T2-weighted while maintaining contrast fidelity. Small white and gray matter structures, as well as blood vessels, were more visible with PSF-optimized VFAs. Quantitative analysis shows that the optimized VFA yields 50% less deviation from a reference PSF (sinc) than the standard VFA. The SNR-optimized VFAs yielded images with significantly improved SNR in a white and gray matter region relative to standard (77.1 vs. 40.7, respectively) as trade-off for elevated image blurring. Conclusion: This study demonstrates the potential of end-to-end learning frameworks to optimize VFA schemes in very long echo trains for 3D FSE acquisition at 7T in terms of PSF and SNR. It paves the way for fast and flexible adjustment of the trade-off between PSF and SNR for 3D FSE.
CRIS-Team Scopus Importer:2025-06-06
Keywords: fast spin echo; optimal control; sequence optimization; ultra high field; variable flip angles

Death by Retrospective Undersampling - Caveats and Solutions for Learning-Based MRI Reconstructions - Rajput, Junaid Rasool; Weinmüller, Simon; Endres, Jonathan; Dawood, Peter; Knoll, Florian; Maier, Andreas; Zaiß, Moritz (Medical Image Computing and Computer Assisted Intervention – MICCAI 2024. 27th International Conference, Marrakesh, Morocco, October 6–10, 2024, Proceedings, Part VII, 2024)
This study challenges the validity of retrospective undersampling in MRI data science by analysis via an MRI physics simulation. We demonstrate that retrospective undersampling, a method often used to create training data for reconstruction models, can inherently alter MRI signals from their prospective counterparts. This arises from the sequential nature of MRI acquisition, where undersampling post-acquisition effectively alters the MR sequence and the magnetization dynamic in a non-linear fashion. We show that even in common sequences, this effect can make learning-based reconstructions unreliable. Our simulation provides both, (i) a tool for generating accurate prospective undersampled datasets for analysis of such effects, or for MRI training data augmentation, and (ii) a differentiable reconstruction operator that models undersampling correctly. The provided insights are crucial for the development and evaluation of AI-driven acceleration of diagnostic MRI tools.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Bloch simulation; Magnetization; Retrospective undersampling

MRzero - Automated discovery of MRI sequences using supervised learning - Loktyushin, A.; Herz, K.; Dang, N.; Glang, F.; Deshmane, A.; Weinmüller, Simon; Dörfler, Arnd; Scholkopf, B.; Scheffler, K.; Zaiss, M. (Magnetic Resonance in Medicine, 2021)
Purpose A supervised learning framework is proposed to automatically generate MR sequences and corresponding reconstruction based on the target contrast of interest. Combined with a flexible, task-driven cost function this allows for an efficient exploration of novel MR sequence strategies.
CRIS-Team WoS Importer:2021-04-16

MR-zero meets FLASH – controlling the transient signal decay in gradient- and RF-spoiled gradient echo sequences - Weinmüller, Simon; Endres, Jonathan; Dang, Hoai Nam; Stollberger, Rudolf; Zaiß, Moritz (Magnetic Resonance in Medicine, 2025)
Purpose: The complex signal decay during the transient FLASH MRI readout can lead to artifacts in magnitude and phase images. We show that target-driven optimization of individual RF flip angles and phases can realize near-ideal signal behavior and mitigate artifacts. Methods: The differentiable end-to-end optimization framework MR-zero is used to optimize RF trains of the FLASH sequence. We focus herein on minimizing deviations from the ideally spoiled signal by using a mono-exponential Look–Locker target. We first obtain the transient FLASH signal decay substructure, and then minimize the deviation to the Look–Locker decay by optimizing the individual (i) flip angles, (ii) RF phases, and (iii) flip angles and RF phases. Comparison between measurement and simulation is performed using Pulseq in 1D and 2D. Results: We were able to reproduce the complex substructure of the transient FLASH signal decay. All three optimization objectives can bring the real FLASH signal closer to the ideal case, with best results when both flip angles and RF phases are adjusted jointly. This solution outperformed all tested conventional quadratic RF cyclings in terms of (i) matching the Look–Locker target signal, (ii) phase stability, (iii) point spread functions ideality, (iv) robustness against parameter changes, and (v) magnitude and phase image quality. Other target functions for the signal could as well be realized, yet their response is not as general as for the Look–Locker target and needs to be optimized for a specific context. Conclusion: Individual flip angle and RF phase optimization improves the transient signal decay of FLASH MRI sequences.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Bloch optimization; extended phase graphs; FLASH; gradient spoiling; MPRAGE; phase distribution graphs; RF spoiling

MR-zero meets RARE MRI: Joint optimization of refocusing flip angles and neural networks to minimize T2-induced blurring in spin echo sequences - Dang, Hoai Nam; Endres, Jonathan; Weinmüller, Simon; Glang, Felix; Loktyushin, Alexander; Scheffler, Klaus; Dörfler, Arnd; Schmidt, Manuel; Maier, Andreas; Zaiß, Moritz (Magnetic Resonance in Medicine, 2023)
Purpose: An end-to-end differentiable 2D Bloch simulation is used to reduce T2 induced blurring in single-shot turbo spin echo sequences, also called rapid imaging with refocused echoes (RARE) sequences, by using a joint optimization of refocusing flip angles and a convolutional neural network. Methods: Simulation and optimization were performed in the MR-zero framework. Variable flip angle train and DenseNet parameters were optimized jointly using the instantaneous transverse magnetization, available in our simulation, at a certain echo time, which serves as ideal blurring-free target. Final optimized sequences were exported for in vivo measurements at a real system (3 T Siemens, PRISMA) using the Pulseq standard. Results: The optimized RARE was able to successfully lower T2-induced blurring for single-shot RARE sequences in proton density-weighted and T2-weighted images. In addition to an increased sharpness, the neural network allowed correction of the contrast changes to match the theoretical transversal magnetization. The optimization found flip angle design strategies similar to existing literature, however, visual inspection of the images and evaluation of the respective point spread function demonstrated an improved performance. Conclusions: This work demonstrates that when variable flip angles and a convolutional neural network are optimized jointly in an end-to-end approach, sequences with more efficient minimization of T2-induced blurring can be found. This allows faster single- or multi-shot RARE MRI with longer echo trains.
CRIS-Team Scopus Importer:2023-07-07
Keywords: DenseNet; joint-optimization; MR-zero; RARE; RF-pulse design; T2-blurring; TSE

Phase distribution graphs for fast, differentiable, and spatially encoded Bloch simulations of arbitrary MRI sequences - Endres, Jonathan; Weinmüller, Simon; Dang, Hoai Nam; Zaiß, Moritz (Magnetic Resonance in Medicine, 2024)
Purpose: An analytical approach to Bloch simulations for MRI sequences is introduced that enables time efficient calculations of signals free of Monte-Carlo noise, while providing full flexibility and differentiability in RF flip angles, RF phases, magnetic field gradients and time, as well as insights into image formation. Theory and Methods: We present an implementation of the extended phase graph (EPG) concept implemented in PyTorch, including an efficient state selection algorithm. This simulation is compared with an isochromat-based Bloch simulation with random isochromat distribution as well as with in vivo measurements using the Pulseq standard. Additionally, different sequences are tested and analyzed using this novel simulation approach. Results: Our simulation outperforms isochromat-based simulations in terms of computation time as well as signal quality, without exhibiting any kind of Monte-Carlo noise. The novel approach allows extracting useful information about the magnetization evolution not available otherwise. Our approach extends the common state-tensor-based EPG simulation approach for the contribution of dephased states including spatial encoding and (Formula presented.) effects, and arbitrary timing. This allows calculation of echo shapes in addition to echo amplitudes only. Our implementation provides full differentiability in all input parameters allowing gradient descent optimization. Simulation of non-instantaneous pulses via hard-pulse approximation is left for future work, as the performance and accuracy characteristics are not yet analyzed. Conclusions: Phase distribution graphs provide fast, differentiable, and spatially encoded Bloch simulations for most MRI sequences. It allows efficient simulation and optimization of arbitrary MRI sequences, which was previously only possible via high isochromat counts.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Bloch simulation; differentiable simulation; extended phase graphs; phase distribution graphs; sequence analysis

Sidebands in CEST MR—How to recognize and avoid them - Schüre, Jan-Rüdiger; Weinmüller, Simon; Kamm, Lukas; Herz, Kai; Zaiß, Moritz (Magnetic Resonance in Medicine, 2024)
Purpose: Clinical scanners require pulsed CEST sequences to maintain amplifier and specific absorption rate limits. During off-resonant RF irradiation and interpulse delay, the magnetization can accumulate specific relative phases within the pulse train. In this work, we show that these phases are important to consider, as they can lead to unexpected artifacts when no interpulse gradient spoiling is performed during the saturation train. Methods: We investigated sideband artifacts using a CEST-3D snapshot gradient-echo sequence at 3 T. Initially, Bloch-McConnell simulations were carried out with Pulseq-CEST, while measurements were performed in vitro and in vivo. Results: Sidebands can be hidden in Z-spectra, and their structure becomes clearly visible only at high sampling. Sidebands are further influenced by B0 inhomogeneities and the RF phase cycling within the pulse train. In vivo, sidebands are mostly visible in liquid compartments such as CSF. Multi-pulse sidebands can be suppressed by interpulse gradient spoiling. Conclusion: We provide new insights into sidebands occurring in pulsed CEST experiments and show that, similar as in imaging sequences, gradient and RF spoiling play an important role. Gradient spoiling avoids misinterpretations of sidebands as CEST effects especially in liquid environments including pathological tissue or for CEST resonances close to water. It is recommended to simulate pulsed CEST sequences in advance to avoid artifacts.
CRIS-Team Scopus Importer:2024-02-16
Keywords: artifacts; CEST; gradient spoiling; phase-cycling; pulsed CEST imaging; pulseq-CEST; sidebands

Snapshot CEST++: Advancing rapid whole-brain APTw-CEST MRI at 3 T - Sedykh, Maria; Liebig, Patrick; Herz, Kai; Fabian, Moritz; Mennecke, Angelika; Weinmüller, Simon; Schmidt, Manuel; Dörfler, Arnd; Zaiß, Moritz (NMR in Biomedicine, 2023)
APTw CEST MRI suffers from long preparation times and consequently long acquisition times ( 5 min). Recently, a consensus on the preparation module for clinical APTw CEST at 3 T was found in the community, and we present a fast whole-brain APTw CEST MRI sequence following this consensus preparation of pulsed RF irradiation of 2 s duration at 90% RF duty-cycle and a B1,rms of 2 μT. After optimization of the snapshot CEST approach for APTw imaging regarding flip angle, voxel size and frequency offset sampling, we extend it by undersampled GRE acquisition and compressed sensing reconstruction. This allows 2 mm isotropic whole-brain APTw imaging for clinical research at 3 T below 2 min. With this sequence, a fast snapshot APTw imaging method is now available for larger clinical studies of brain tumors.
CRIS-Team Scopus Importer:2023-08-04
Keywords: 3T CEST; APTw; brain tumor; compressed sensing; snapshot CEST

The Pulseq-CEST Library: definition of preparations and simulations, example data, and example evaluations - Liebeskind, Alexander; Schüre, Jan-Rüdiger; Fabian, Moritz; Weinmüller, Simon; Schünke, Patrick; Golkov, Vladimir; Cremers, Daniel; Zaiß, Moritz (Magnetic Resonance Materials in Physics Biology and Medicine, 2025)
Objectives: Despite prevalent use of chemical exchange saturation transfer (CEST) MRI, standardization remains elusive. Imaging depends heavily on parameters dictating radiofrequency (RF) events, gradients, and apparent diffusion coefficient (ADC). We present the Pulseq-CEST Library, a repository of CEST preparation and simulation definitions, including example data and evaluations, that provides a common basis for reproducible research, rapid prototyping, and in silico deep learning training data generation. Materials and methods: A Pulseq-CEST experiment requires (i) a CEST preparation sequence, (ii) a Bloch–McConnell parameter set, (iii) a Bloch–McConnell simulation, and (iv) an evaluation script. Pulseq-CEST utilizes the Bloch–McConnell equations to model in vitro and in vivo conditions. Using this model, a candidate sequence or environment can be held constant while varying other inputs, enabling robust testing. Results: Data were compared for amide proton transfer weighted (APTw) and water shift and B1 (WASABI) protocols using a five-tube phantom and simulated environments. Real and simulated data matched anticipated spectral shapes and local peak characteristics. The Pulseq-CEST Library supports similar experiments with common sequences and environments to assess new protocols and sample data. Discussion: The Pulseq-CEST Library provides a flexible mechanism for standardizing and prototyping CEST sequences, facilitating collaborative development. With the capability for expansion, including open-source incorporation of new sequences and environments, the library accelerates the invention and spread of novel CEST and other saturation transfer approaches, such as relayed NOEs (rNOEs) and semisolid magnetization transfer contrast (MTC) methods.
CRIS-Team Scopus Importer:2025-04-11
Keywords: Computer assisted; Computer simulation; Image processing; Imaging; Magnetic resonance imaging; Phantoms; Software